2014
DOI: 10.1590/0004-2730000003209
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between polymorphisms in the UBASH3A gene and autoimmune thyroid disease: a case control study

Abstract: Objective: The aim of this study was to investigate UBASH3A gene variation association with autoimmune thyroid disease and clinical features in a Chinese Han population. Subjects and methods: A total of 667 AITD patients (417 GD and 250 HT) and 301 healthy controls were genotyped for two single nucleotide polymorphisms (SNPs) rs11203203, rs3788013 of UBASH3A gene, utilizing the Matrix Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometer (MALDI-TOF-MS) Platform. Results: Between the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Meanwhile, oxidative stress occurs by the imbalance between prooxidants and antioxidants, which causes damage to macromolecules, disruption of ions in redox signaling, and alterations of proteins [9]. Many studies found an association between increased oxidative stress and HT [10]. Though, the exact link between them is still debated [11].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, oxidative stress occurs by the imbalance between prooxidants and antioxidants, which causes damage to macromolecules, disruption of ions in redox signaling, and alterations of proteins [9]. Many studies found an association between increased oxidative stress and HT [10]. Though, the exact link between them is still debated [11].…”
Section: Introductionmentioning
confidence: 99%